Effect of Wuzhuyu Decoction on alcoholic gastric ulcer and its mechanism - GAO Ruiyang, LI Jingyao, LI Pingxiang, GE Keli (精准医学杂志)
Objective To investigate the effect of Wuzhuyu Decoction (WZYD) on alcoholic gastric ulcer and its mechanism. Methods A total of 120 female KM mice, aged 8 weeks, were randomly divided into normal control group (group A), model control group (group B), ranitidine group (group C), and low-, middle-, and high-dose WZYD groups (groups D-F), with 20 mice in each group. The mice in groups A and B were given distilled water (10 mL/kg) at room temperature by gavage, those in group C were given ranitidine (30 mg/kg) by gavage, and those in groups D-F were given WZYD by gavage at a dose of 5, 10, and 20 mL/kg, respectively. After 7 consecutive days of intragastric administration, 10 mice were selected from each group, and serum was collected under aseptic conditions for cell experiments, and the remaining mice were still given distilled water or the drug by gavage for another 21 days. Body weight and food intake of the mice in each group were recorded on days 7, 14, 21, and 28. On day 29, serum, gastric juice, and gastric tissue samples were collected; gastric morphology was observed with the naked eye, and HE staining was used to observe the histopathological changes of gastric mucosa; the volume, pH value, and total acidity of gastric juice were measured; ELISA was used to measure the serum levels of IL-6, IL-10, TNF-α, and PGE2; Western blot (WB) was used to measure the expression of PI3K/Akt/NF-κB pathway-related proteins in gastric mucosa; biochemical assays were used to measure the levels of MDA, CAT, SOD, and GSH-Px in gastric mucosa. Human gastric mucosal epithelial cells (GES-1) were divided into groups a1-e1 and a2-f2. The cells in groups a1-e1 were treated with the aseptic serum from groups A, C, D, E, and F, respectively. The cells in groups b2-f2 were treated with 0.8 mol/L ethanol, while those in group a2 were treated with an equal volume of PBS; after 4 hours of treatment, the cells in groups a2-f2 were treated with the aseptic serum from groups A-F. CCK-8 assay was used to measure cell viability in each group. Results The animal experiment showed that compared with group B, groups C-F had a significant increase in body weight at different time points, along with varying degrees of improvements in congestion, edema, punctate ulcers, and inflammatory cell infiltration of gastric mucosa, significant reductions in the volume and total acidity of gastric juice, a significant increase in the pH value of gastric juice, significant reductions in the serum levels of IL-6, TNF-α, and PGE2 and p-AKT/AKT ratio and MDA level in gastric mucosal tissue, and significant increases in the serum level of IL-10 and the levels of SOD and GSH-Px in gastric mucosa; groups C, E, and F had a significant increase in food intake on days 14, 21, and 28 and a significant reduction in the ratio of P65 in the nucleus to P65 in the cytoplasm; groups C and E had a significant increase in the level of CAT in gastric mucosal tissue; groups D-F had a significant reduction in p-PI3K/PI3K ratio in gastric mucosal tissue; group E and F had a significant increase in p-IκBα/IκBα ratio in gastric mucosal tissue (F=3.4-1 013.0,q=4.1-78.7,P<0.05). CCK-8 assay showed that there was no significant difference in cell viability between groups c1-e1 and group a1 at any time point (P>0.05), and groups c2-f2 had a significantly higher cell viability than group b2 at 12, 24, and 48 hours of culture (F=15.5-146.1,q=4.6-22.3,P<0.05). Conclusion WZYD can exert a protective effect against alcoholic gastric ulcers by modulating the PI3K/Akt/NF-κB signaling pathway, regulating inflammatory cytokines, and inhibiting oxidative stress.